PENGARUH TEKNOLOGI KECERDASAN BUATAN (AI) PERSPEKTIF MARTIN HEIDEGGER - Fitriani; Veranita Indah, Astrid; Mubarak (Aqidah-ta: Jurnal Ilmu Aqidah, 2024)
This article addresses the problem of the influence of artificial intelligence from the perspective of Martin Heidegger, a German philosopher famous for his contributions to human thought. His critique of technology is contained in his seminal work, The Question of Technology, which outlines the nature of technology and its relationship to human beings. Technology has significantly affected human life from the way we live, work and interact. This research uses a qualitative method with literature analysis to understand the meaning and influence of technology on human existence in the modern era. The main data is obtained from Martin Heidegger's writings and works, as well as references from related scholarly works. The results of this study show that Martin Heidegger believes that technology is able to bring human beings into a frame that can limit the way of thinking and acting, especially artificial intelligence (AI) with its ability to manipulate and master human thought. Heidegger's view can provide new insights into how we view technology.